Variations in immunofluorescent antibody response against Trichobilharzia and Schistosoma antigens in compatible and incompatible hosts - Kourilová, P; Kolárová, L (Parasitology research, 2002)
Schistosome cercariae are able to penetrate into the skin of various vertebrate hosts. However, in contrast to the compatible host, the infection of incompatible hosts results in the death of parasites at various intervals post-infection. In order to compare the immune responses in both types of host infected with Trichobilharzia regenti, Trichobilharzia szidatior Schistosoma mansoni, antibody responses against various T. regenti, T. szidatiand S. mansonischistosome developmental stages were studied. Indirect immunofluorescence tests (IFAT) demonstrated no species-specific reactivity of human, mouse or duck immune sera with cercarial surfaces. Study of the cercarial glands also gave no significant results. However, differences were found in schistosomular and adult antigens: only the sera of compatible hosts recognised schistosomular and adult gut associated antigens in homologous as well as heterologous systems. Based on the presented data, our study supports the use of IFAT for the serological differentiation of schistosomiasis and cercarial dermatitis caused by bird schistosomes.
Keywords: Antibodies, Helminth; Animals; kachny; myši bezsrsté; Antigens, Helminth; Ducks; Mice, Hairless; protilátky helmintové; Host-Parasite Interactions; fluorescenční protilátková technika; Schistosomatidae; Mice; Fluorescent Antibody Technique; interakce hostitele a parazita; Mice, Inbred BALB C; myši; ovum; stadia vývoje; antigeny helmintové; myši inbrední BALB C; Ovum; Life Cycle Stages; zvířata; Schistosoma mansoni